The library boys [videorecording (DVD)] - Borg, Zane; Kenny, Jack; Barrett, Mia; Kenny, Joe (Filmhub, 2025)
Three Aussie mates navigate their final year of high school, facing heartbreak, friendship, and the chaos of growing up. Amidst wild parties, unwanted body hair, and Shakespeare, they discover what it truly means to grow up.